Histone H3K36M mutation and trimethylation patterns in chondroblastoma. Issue 2 (4th November 2018) - Lu, Chuanyong; Ramirez, Daniel; Hwang, Sinchun; Jungbluth, Achim; Frosina, Denise; Ntiamoah, Peter; Healey, John; Zhu, Guo; Chen, Wen; Klein, Michael; Hameed, Meera
Abstract : Aims: Histones are essential components of chromatin, and mutations in histones lead to alterations in methylation and acetylation, which play an important role in tumorigenesis. Most of the chondroblastomas harbour the H3K36M mutation. With the availability of a mutation‐specific antibody, we sought to assess the sensitivity of this antibody and the alterations of histone methylation in a series of chondroblastoma cases. Methods and results: Immunohistochemical staining with antibodies against H3K36M, trimethylated histones (H3K27me3 and H3K36me3) and an osteoblastic marker (SATB2) was performed on 27 chondroblastomas from 27 patients. The clinical and radiological characteristics of each patient were reviewed. All 27 tumours showed typical radiological and histological features of chondroblastoma, with a subset of cases showing secondary aneurysmal bone cyst changes (11/27), giant‐cell‐rich foci (4/27), and matrix‐rich areas mimicking chondromyxoid fibroma (1/27). All except one case (26/27, 96%) showed positive H3K36M immunostaining (nuclear). In the majority of cases, there was a diffuse staining pattern. Immunohistochemical staining for H3K27me3 and H3K36me3 showed a heterogeneous staining pattern in all cases, regardless of mutation status. None of the cases showed loss of positivity or diffuse positivity. Focal or diffuse SATB2 expression was seen in 21 of 26 tumours (81%). Conclusion: Our results demonstrate that the vast majority of chondroblastomas are positive for H3K36M by immunohistochemical analysis, confirming its diagnostic value. H3K27me3 expression and H3K36me3 expression are heterogeneous in these tumours.